Pengalihan Saham Mayoritas Badan Usaha Pelaksana Pada Proyek KPBU Ditinjau dari Aspek Persaingan Usaha (Studi Kasus: Proyek Kpbu Tppas Lulut Nambo) - Winda Tania (UNES Law Review, 2023)
This article analyses how the transfer of a majority of shares in an Implementing Business Entity (BUP) was applied in the Lulut Nambo Waste Processing and Management Site Private Public Partnership (KPBU TPPAS) Project from the viewpoint of business competition. The exemption from the applicability of the Prohibition of Monopolistic Practices and Unfair Business Competition Act Law No. 5 of 1999 was the Government of Indonesia’s attempt to strike a balance in the need for the state’s ownership of production sectors which control the livelihood of many people with due attention to the balance between the interests of business actors and the public interest. This article has been compiled using a doctrinal research methodology. The prequalification stage and tender process is a form of competitive principle in PPP projects, in that the implementation of the PPP project begins with the procurement of a partner through a fair, open, and transparent selection stage with due attention to the principles of fair business competition. The transfer of a majority of shares in the Implementing Business Entity as the winner of the Lulut Nambo KPBU TPPAS Project to another party which did not take part in the prequalification stage and the tender process could be viewed as special treatment for that party according to the provisions of the laws and regulations. Nevertheless, this did not breach the business competition aspects because BUP fulfilled the elements for exemption for business actors which have statutory monopolies.